ANALYSIS OF TOURISM DESTINATIONS OF HOK LAY KIONGTEMPLE AND THE IMPACT FOR THE COMMUNITY - Noegroho, Aditya; Musthofa, Budiman Mahmud (UI Scholars Hub, 2022)
The existence of the tourism sector is closely related to the SDGs or Sustainable Development Goals (sustainable development). The number of tourist visits is one element that can ensure an increase in the economic contribution of tourism. Researchers are interested in knowing the analysis of Hok Lay Kiong temple tourist destinations in Bekasi City using the theory of attractions, accessibility, amenities and ancillary and their impact on local residents. The method applied in this research is a qualitative descriptive method. Research shows that accessibility to get to Hok Lay Kiong Temple can be reached easily by using the K02, K05, P9BT, TP-1 bus or using the BEKASI LINE train. Attractions or performances at the Hok Lay Kiong Temple are celebrating the Chinese New Year, Capgomeh celebrations, bad luck rituals carried out on the Bekasi River and hitting the drum, playing at the beginning of the month (full moon) and at the end of the month (small moon). And the last one is ancillary at the Hok Lay Kiong Temple, namely there is a vehicle parking area, prayer room, bathroom / MCK, lodging and many others. The impacts that can be felt by residents around the Hok Lay Kiong Temple include economic growth for local residents, the surrounding community becomes more open and respects the beliefs of others, eliminates negative prejudices against a certain ethnicity, cross-cultural awareness that can increase mutual understanding and respect. understand from different cultural backgrounds.